Impact of Modern Civilization on National Culture (Eurasian Journal of Humanities and Social Sciences, 2023)
The article analyzes issues related to the change of some structural elements of national culture and the impact of the change process on social relations. It has been scientifically and theoretically studied that the change of national culture is the main and leading trend of modern society